Analysis of the Association Between Reward and Workplace Spirituality with Employee Performance - Khairawati, Salihah; Nugroho Hadi, Sugeng; Efendi, Bahtiar; Candra Nurhayati, Eny (Asian Journal of Management Analytics, 2024)
It is unique when you want to know the effect of rewards and workplace spirituality on employee performance. Why? Because rewards, in the form of compensation and promotions, are proper if they have an effect on employee performance, but if only in the form of praise, it is not so significant. Likewise, workplace spirituality is very tentative. That is the uniqueness of this research. The object of research is at Waroeng Steak and Shake Yogyakarta. The research was conducted with a quantitative descriptive associative approach. The research instrument was a questionnaire distributed to a total of 120 respondents (employees). The results showed that there was a significant influence on the reward variable (0.580) and workplace spirituality (0.000) on employee performance; with the equation Y = 4.038 + 0.580 X1 + 0.682 X2. Determination (Adjusted R2) is 0.660 or 66%, which indicates that 66% of the value of Y is explained by X1 and X2 and the remaining 44% is explained by other factors. Another finding was that the company's efforts in providing rewards and in creating a spiritual workplace received a positive response from employees.